Students’ Views on Teachers’ Interpersonal Competence in University Classrooms - Alfiantoro, Dion; Purwanti, Eko; Hermayawati, Hermayawati; Fachry, Naufal; Fitriamin, Muh. Aidil; Dipayana, Rayhan Anwar Purba (Universitas Muhammadiyah Yogyakarta, 2026)
This study investigated students’ perceptions of their teachers’ interpersonal skills at a popular private university in Yogyakarta. Interpersonal skills, including communication, rapport building, motivation, and teamwork, are essential to creating an effective and supportive educational environment. This study aimed to understand how students perceive these skills in their teachers and how these perceptions impact their overall academic experience. Data were collected through qualitative interviews with students from three various faculties. The interviews provided deeper insights into specific experiences and examples where teachers’ interpersonal skills significantly impacted student engagement and learning outcomes. The findings revealed that most teachers effectively communicated with students, providing clear answers and delivering course material in an engaging, cheerful manner, which reflected their strong interpersonal communication skills. Additionally, students reported having positive relationships with their teachers, attributing this to effective communication and enjoyable classroom experiences. These positive relationships boosted students' motivation and enthusiasm for learning, while also reducing procrastination. The study further discovered that teachers consistently motivated students by sharing personal stories, using motivational language, and fostering teamwork in the classroom. This study suggests that universities should invest in professional development programs that focus on improving teachers' interpersonal skills, as this significantly benefits to the overall educational environment